A Study of Qualitative Bio Chemical Analysis of "Neer Perukki Chooranam" - Nushrath Roshana, M. (Faculty of Engineering and Technology, Annamalai University, 2024)
Siddha system is an ancient Indian traditional medical system which evolved in South India, chiefly in Tamil Nadu and North, East of Srilanka. The current accepted modern medicine has gradually developed over the years by scientific and observational efforts of scientists. However, the basis of its development remains rooted in traditional medicine and therapies. In the Siddha system, the raw materials such as plant, mineral and animal resources are acquired from the natural surroundings. They have been used extensively for many centuries after thorough evaluation of the drug by traditional way. Siddha system of medicine consists of 64 types of unique preparations. In these 32 internal medicines and 32 external medicines. Chooranam is one formulation of Internal medicine. Neer perukki Chooranam is a herbo - mineral formulation in Siddha Medicine, consists of eight ingredients. Need for Evidence Based Medicine is high degree of variation in medical practice despite doctors being trained with the same curriculum, with the medical care getting more complex and expensive. It is important to know the best possible care and whenever possible cost effective treatment. Regarding for this aim, the basic step made up to analysis the biochemical of Neer Perukki Chooranam to standard the drug: which detects the presence of chloride, calcium, starch, sulphate, ferrous iron, unsaturated compound, tannic acid, reduced sugar, amino acid. From the bio chemical analysis, the research drug "Neer Perukki Chooranam" is proofing as a very effective and efficacy for the indications of Neerkattu, Soabai and Makotharam which are mentioned in the Pharmacopia of Indian Medicine.
Keywords: Qualitative; Bio chemical; Siddha Medicine; Neer perukki chooranam